Studying the Effect of Alpha-Tocopherol on Cell Proliferation and Apoptosis in Rat Bone Marrow Mesenchymal Stem Cells - Malek Soleimani Mehranjani; Majid Mahdiyeh; Atena Sadat Azimi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2015)
Abstract Background: Alpha-tocopherol, as a strong antioxidant, plays an important role in testraining free radicals. The aim of this study was to investigate the effect of Alpha-tocopherol on cell proliferation and restraining apoptosis in rat bone marrow mesenchymal stem cells. Materials and Methods: In this research study, the rat bone marrow mesenchymal stem cells were extracted under sterile conditions using flashing-out method. At the end of the third passage, cells were divided into groups of control and Alpha-tocopherol with doses of 15 and 25 µM and were treated in the osteogenic media cell medium containing 10% fetal bovine serum, 10 mM β-glycerol phosphate, 10 nM dexamethasone and 50 µg/ml ascorbic 3-phosphate] for a period of 21 days. Then, cell proliferation, DNA damage, expression of Bcl-2 and Bax genes and the morphologic changes of the cells were investigated during the procedure of osteogenesis. Data were analyzed using one-way ANOVA and means difference was considered significant at p<0.05. Results: Cell proliferation, the size of nuclei diameter and expression of anti-apoptotic Bcl-2 gene showed a significant increase in mesenchymel stem cells treated with Alpha-tocopherol (p<0.05) in a dose dependent manner compared to the control cells. Also, cytoplasm extension was seen in the cells treated with Alpha-tocopherol, compared to the control group. Since Alpha-tocopherol causes a significant decrease in DNA damage and the expression of apoptotic Bax gene, compared to the control group, therefore it can suppress apoptosis in bone marrow mesenchymal stem cells, in a dose dependent manner.